Learning Analytics and Survey Data Integration in Workload Research - Evgenia Samoilova; Florian Keusch; Tobias Wolbring (Forum Neue Medien in der Lehre Austria, 2017)
While Learning Analytics (LA) has a lot of potential, educators sometimes doubt whether it is worth to invest in the analysis of LA and whether its use yields additional insights. Drawing on data from a pilot study, we illustrate an application of LA for the evaluation of student workload in online or blended learning courses. Although measuring student workload is essential for optimizing learning, workload research is still under development. The study compares results provided by two data sources: viewing activity logs and a weekly evaluation survey. The results indicate that self-reported data provide higher estimates of workload than LA. Moreover, the two measures are only weakly correlated. The results should be replicated with a larger sample size, different sub-populations, and in different contexts. 29.03.2017 | Evgenia Samoilova, Florian Keusch & Tobias Wolbring